Targeted but (not) toxic? TLTRO and financial stability - Marcel Barmeier (Oesterreichische Nationalbank (OeNB), 2025)
As TLTRO programs provide a direct incentive to increase lending, investigating the level of prudence applied by banks in making lending decisions is of high relevance. Relying on loan-level data, I evaluate the riskiness of lending by applying estimations in a difference-in-differences setting around the cut-off of the TLTRO lending period. Investigating various risk-taking strategies, I show that participation in TLTRO operations is not associated with an increase in PDs, defaults or loans overdue. Even banks that only narrowly fulfilled the lending requirements to benefit from the lowest interest rate applied to TLTRO funding did not engage in higher risk-taking.
Keywords: E44; E51; E52; E58; G21; 330; Monetary policy transmission; funding-for-lending; risk-taking channel; financial stability; TLTRO